Extraction, Phytochemical Profiling, FTIR Characterization, and Textile Application of Natural Dyes from the Bark of Ficus religiosa and Bombax ceiba - Bhandari, Arjun; Adhikari, Rupa; Pokharel, Ramita (BMC Journal of Scientific Research, 2025)
Synthetic dyes commonly used in the textile industry pose significant environmental and health concerns due to their toxic, non biodegradable nature. In response, natural dyes from plant sources are gaining attention as sustainable alternatives. This study investigates natural dyes derived from the barks of Ficus religiosa (Peepal) and Bombax ceiba (Semal), focusing on their extraction, characterization, and textile application. Dyes were extracted using aqueous and organic solvents, and subsequently characterized through phytochemical screening and Fourier Transform Infrared (FTIR) Spectroscopy to identify the key bioactive constituents and functional groups. The extracted dyes were then applied to cotton and silk fabrics, with evaluations for colourfastness and mordanting behaviour. Phytochemical analysis confirmed the presence of tannins, flavonoids, and anthraquinones, while FTIR spectra validated the presence of chromophoric functional groups. The dyed fabrics exhibited vibrant colours with favourable fastness properties, demonstrating both aesthetic appeal and functional performance. These findings suggest eco-friendly alternatives to synthetic dyes. The novelty of this work lies in its integration of phytochemical profiling, FTIR-based characterization, and practical textile application, offering a comprehensive approach to natural dye research.